Mixture Effects of Tryptophan Intestinal Microbial Metabolites on Aryl Hydrocarbon Receptor Activity - Vrzalová, Aneta; Pečinková, Petra; Illés, Peter; Gurská, Soňa; Džubák, Petr; Szotkowski, Martin; Hajdúch, Marián; Mani, Sridhar; Dvořák, Zdeněk (International journal of molecular sciences, 2022)
Aryl hydrocarbon receptor (AHR) plays pivotal roles in intestinal physiology and pathophysiology. Intestinal AHR is activated by numerous dietary, endogenous, and microbial ligands. Whereas the effects of individual compounds on AHR are mostly known, the effects of real physiological mixtures occurring in the intestine have not been studied. Using reporter gene assays and RT-PCR, we evaluated the combinatorial effects (3520 combinations) of 11 microbial catabolites of tryptophan (MICTs) on AHR. We robustly (n = 30) determined the potencies and relative efficacies of single MICTs. Synergistic effects of MICT binary mixtures were observed between low- or medium-efficacy agonists, in particular for combinations of indole-3-propionate and indole-3-lactate. Combinations comprising highly efficacious agonists such as indole-3-pyruvate displayed rather antagonist effects, caused by saturation of the assay response. These synergistic effects were confirmed by RT-PCR as CYP1A1 mRNA expression. We also tested mimic multicomponent and binary mixtures of MICTs, prepared based on the metabolomic analyses of human feces and colonoscopy aspirates, respectively. In this case, AHR responsiveness did not correlate with type of diet or health status, and the indole concentrations in the mixtures were determinative of gross AHR activity. Future systematic research on the synergistic activation of AHR by microbial metabolites and other ligands is needed.
Keywords: tryptophan metabolites; Tryptophan; messenger RNA; Indoles; tryptofan; ligandy; indole derivatives; Intestines; aryl hydrocarbon receptor; lidé; Receptors, Aryl Hydrocarbon; cytochrom P-450 CYP1A1; střeva; pyruváty; Ligands; microbiome; mimic mixtures; RNA, Messenger; Humans; Pyruvates; indoly; propionáty; receptory aromatických uhlovodíků; Propionates; Cytochrome P-450 CYP1A1